Science Teaching through Problematization: students' perceptions about Drosophila melanogaster life cycle (Research, Society and Development, 2022)
The present study used the Problematization Methodology with the Maguerez Arch (MP/AM) to verify students’ perception about the insect’s life cycle. For this, Drosophila melanogaster, popularly known as fruit fly, was used as model. In addition to its use as an experimental model, this insect has been used as a didactic model to support the teaching and learning process. This activity was developed with eighth grade students from a public elementary school in Uruguaiana/RS city. Data were collected through notes taken by participants during the activities, and these were analyzed and categorized. The activity was developed over three weeks, divided into 2 hours/class per week, in the curricular component of science. Results indicated that MP/AM, together with the proposed didactic model, served as a facilitator for the teaching-learning process. Furthermore, the use of MP/AM, allied to D. melanogaster model, made the insects life cycle teaching more interesting and dynamic, as it enabled students to develop skills such as criticality and autonomy. In this way, we infer that diversified strategies for Science Teaching can serve as propellers for the learning improvement, and consequently, for the formation of subjects more able to problematize and critically analyze the world around them.